" " ( 2)

 .


) ( 114)



) ( 1522)




1
A B
Pc m11, Z = 1A2B(1; m)
A = B
Pc m11, Z = 3A(1, m)
2
A B
Pcmm2, Z = 1A2B(m; mm2)
A = B
Pcmm2, Z = 3A(m, mm2)
3
A B
Pc 2mm, Z = 1AB(2mm; 2mm)
A = B
Pc mmm, Z = 2A(2mm)
4
A B
Pc cm21, Z = 2AB(m; m)
A = B
Pc cm21, Z = 4A(m2)
5
A B
Pc c2m, Z = 2AB(m; m)
A = B
Pc c2m, Z = 4A(m2)
6
A B
Pc mmm, Z = 1A4B(m; mmm)
A = B
Pc mmm, Z = 5A(m, mmm)
7
A B
Pc cmm, Z = 2AB(2mm; 2mm)
A = B
Pc cmm, Z = 4A([2mm]2)
8
A B
Pc cmm, Z = 2AB(2mm; 2mm)
A = B
Pc mmm, Z = 2A(2mm)
9
A B
Pc cmm, Z = 2A2B(m; 2mm)
A = B
Pc cmm, Z = 6A(m, 2mm)
10
A B
Pc ccm, Z = 2A2B(m; 222)
A = B
Pc ccm, Z = 6A(m, 222)
11
A B
Pc 4122, Z = 4AB(2; 2)
A = B
Pc 4122, Z = 8A(22)
12
A B
Pc 42/mmc, Z = 2AB2(mmm; 2mm)
A = B
Pc 42/mmc, Z = 6A(mmm, 2mm)
13
A B
Pc 42/mmc, Z = 2AB2(-42m; 2mm)
A = B
Pc 42/mmc, Z = 6A(-42m, 2mm)
14
A B
Pc 211, Z = 1AB2(2; 1)
A = B
Pc 312, Z = 3A(2)
15
A B
Pl 1, Z = 1AB(1; 1)
A = B
Pl -1, Z = 2A(1)
16
A B
Pl 11m, Z = 1AB(m; m)
A = B
Pl 112/m, Z = 2A(m)
17
A B
Pl 112, Z = 1AB(2; 2)
A = B
Pl 112/a, Z = 2A(2)
18
A B
Pl 112/m, Z = 1AB(2/m; 2/m)
A = B
Pl 112/m, Z = 1A(2/m)
19
A B
Pl 112/m, Z = 1AB(2/m; 2/m)
A = B
Cl mmm, Z = 2A(mmm)
20
A B
Pl -6m2, Z = 1AB(-6m2; -6m2)
A = B
Pl 6/mmm, Z = 2A(-6m2)
21
A B
Pl -6m2, Z = 1AB2(-6m2; 3m)
A = B
Pl -6m2, Z = 3A(-6m2, 3m)
22
A B
Pl 3m1, Z = 1AB(3m; 3m)
A = B
Pl -3m1, Z = 2A(3m)


""
 .